The influence of self-esteem and role stress on job performance of technical college employees - Kanayo, Damian Ogbu (International Journal of Online and Distance Learning, 2017)
Purpose: The authors examined the influence of self-esteem and role stress on job performance of technical college employees. Research design: two sets of hypotheses were proposed. The first accessed the effect of self-esteem on job performance and the second focused on role stress on job performance. Participants consisted of 162 employees drawn from technical teachers and workshop attendants in selected technical colleges in Rivers and Bayelsa states. Questionnaire was the research instrument for data collection. To test the hypotheses, Structural equation modeling (SEM), were implemented. Findings: The result of the study indicated that there is significant negative effect of self-esteem, Role ambiguity and role overload on job performance of employees in technical colleges Policy implications: Findings in this research indicates that college authorities should focus efforts at boosting self-esteem, since high self-esteem causes many positive outcomes. The study would be very useful to employees and students of technical colleges.